2021
DOI: 10.3390/toxins13060428
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Optimal Dose of Botulinum Toxin A in Post-Stroke Lower Extremity Spasticity: A Systematic Review and Meta-Analysis

Abstract: Post-stroke spasticity impedes patients’ rehabilitation progress. Contradictory evidence has been reported in using Botulinum Neurotoxin type A (BoNT-A) to manage post-stroke lower extremity spasticity (PLES); furthermore, an optimum dose of BoNT-A for PLES has not yet been established. Therefore, we conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to identify the efficacy and optimal dose of BoNT-A on PLES. "Meta" and "Metafor" packages in R were used to analyze the data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Self-reported pain in CCP is the primary determinator for diminished quality of life [ 4 , 5 ], [ 38 , 39 , 40 ]. In part 1 of this study, we were unable to detect an expected BoNT dose-dependent decrease in spasticity [ 41 , 42 , 43 , 44 , 45 ]. At first glance, this is unexpected because we usually assume a relationship between the dosing of BoNT and modulation/reduction of spasticity.…”
Section: Discussionmentioning
confidence: 75%
“…Self-reported pain in CCP is the primary determinator for diminished quality of life [ 4 , 5 ], [ 38 , 39 , 40 ]. In part 1 of this study, we were unable to detect an expected BoNT dose-dependent decrease in spasticity [ 41 , 42 , 43 , 44 , 45 ]. At first glance, this is unexpected because we usually assume a relationship between the dosing of BoNT and modulation/reduction of spasticity.…”
Section: Discussionmentioning
confidence: 75%
“…Doan et al published a systematic review and meta-analysis to evaluate the efficacy and optimal dose of BoNT-A in the post-stroke lower extremity spasticity (PLES). They found that doses of approximately 300 U of BoNT-A could be the preferable dosage for spastic plantar flexors, which is the most common pattern of PLES [ 27 ]. Interestingly, in our study, we observed that after injecting large doses of BoNT-A into a relatively small muscle group, the women’s external sphincter, the patients showed a significant improvement in lower urinary tract symptoms accompanied by a lower incidence of side effects such as incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…Two tables were created, one for systematic reviews ( Table 1 ) and one for meta-analyses ( Table 2 ), showing the characteristics of the studies included in this umbrella review. Of the total number of included studies, 12 were systematic reviews [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] and 16 were meta-analyses [ 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 34 , 35 , 36 , 37 , 38 ]. The studies included in this umbrella review were published between 2001 and 2023.…”
Section: Resultsmentioning
confidence: 99%
“…The duration of intervention ranged from 0 to 48 months. Almost all the included studies used the MAS [ 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 38 , 42 ], five used the Tardieu Scale [ 11 , 18 , 24 , 31 , 32 ], and five used the Modified Tardieu Scale [ 13 , 19 , 25 , 27 , 33 ].…”
Section: Resultsmentioning
confidence: 99%